Nurse leadership: Sustaining a culture of safety - Haskins, Helena E.M.; Roets, Lizeth (Health SA = SA Gesondheid, 2022)
BackgroundNurse leaders are essential to manage nursing practices that affect patient safety; therefore, they must create and sustain a sound safety culture in a diverse cultural environment.AimTo describe the specific actions required by nurse leadership to enhance the sustainability of a safety culture in hospitals and among a diverse nursing team, ultimately improving patient outcomes.SettingTwo hospitals in the United Arab Emirates (UAE) were selected purposively, based on the diversity of the nursing team.MethodsA quantitative design, using Reason’s safety culture framework and Ekenedo’s behavioural safety model, formed the theoretical background of this study to identify the safety culture and positive work environment that exist among culturally diverse nurses. Thirty-four nurse managers and 417 nurses were conveniently selected to participate. Various instruments were used to gather hospital outcomes and other data from respondents pertaining to their demographics, patient safety, positive work environments and safety culture.ResultsFindings received from the nursing team describe the correlation between patient safety, a diverse nursing workforce and positive work environment affecting a safety culture and promoting positive patient outcomes.ConclusionNurse leaders’ integration of specific actions to address the system, as well as diverse nursing teams’ behavioural practices, create a patient care environment that adequately contributes to safety culture practices and enhances positive patient outcomes, which are essential for a culture of safety.ContributionThe study contributes by providing a structured integration of specific actions for nurse leaders to sustain practices ensuring positive patient outcomes.